2011
DOI: 10.1111/j.1600-0625.2011.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Annotation of sheep keratin intermediate filament genes and their patterns of expression

Abstract: Keratin IF (KRT) and keratin-associated protein genes encode the majority of wool and hair proteins. We have identified cDNA sequences representing nine novel sheep KRT genes, increasing the known active genes from eight to 17, a number comparable to that in the human. However, the absence of KRT37 in the type I family and the discovery of type II KRT87 in sheep exemplify species-specific compositional differences in hair KRT genes. Phylogenetic analysis of hair KRT genes within type I and type II families in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 38 publications
4
51
1
Order By: Relevance
“…Our results validate earlier findings which relied on indirect labelling methods, in particular those of Yu and colleagues' mRNA labelling work on follicles of Wiltshire sheep 11 . Also, in the general sense that wool and human scalp and beard follicles share a good deal of common biology, we find that our results follow a similar pattern to the immunocytochemistry and mRNA results of Langbein and colleagues 7 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results validate earlier findings which relied on indirect labelling methods, in particular those of Yu and colleagues' mRNA labelling work on follicles of Wiltshire sheep 11 . Also, in the general sense that wool and human scalp and beard follicles share a good deal of common biology, we find that our results follow a similar pattern to the immunocytochemistry and mRNA results of Langbein and colleagues 7 .…”
Section: Discussionsupporting
confidence: 94%
“…Also, in the general sense that wool and human scalp and beard follicles share a good deal of common biology, we find that our results follow a similar pattern to the immunocytochemistry and mRNA results of Langbein and colleagues 7 . As with those earlier studies, we conclude from our results that keratins first appear in the cortex at the beginning of Zone B, with K35 and K85 being the first to appear followed shortly after by K31 [8][9][10][11] . The proteomic methods will continue to detect proteins after expression has stopped, provided the proteins are not destroyed.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Keratin-based wound care devices have been approved for use in several regions of the world including use as a topical agent for wound care (9). With keratin intermediate filaments as major components, ovine wool shares high similarity with human hair (12). Clinicians using wool-derived oxidized keratin have found improved healing for hard to heal chronic wounds (13).…”
Section: Introductionmentioning
confidence: 99%
“…Two major types are present, the intermediate filamentforming keratin proteins and the keratin associated proteins (KAPs) [2]. The keratins are further divided into two types, the acidic Type Is and the neutral-basic Type IIs [3][4][5][6]. The KAPs have been divided into three classes: high sulphur proteins (HSPs), ultra-high sulphur proteins (UHSPs) and high glycinetyrosine proteins (HGTPs) [2], though from studies of human hair some new KAPs have been identified that do not fit into any of these categories [7].…”
Section: Introductionmentioning
confidence: 99%